The Main Indicators of Tourism in Uzbekistan Before the Pandemic - Ruzikulovich, Shodiev Sanjar; Jahongir, Yarashev (Research Parks Publishing LLC, 2022)
The epidemiological turmoil observed in recent years around the world has had a significant impact on all areas of human activity, including tourism around the world. According to statistics from the World Tourism Organization, tourism in the world in 2020 clearly showed a decrease of 74% compared to the previous year. The organization analyzed tourism indicators in 2021 and announced its forecasts for when tourism will return to its pre-pandemic status. This article focuses on the pre-pandemic indicators of the Republic of Uzbekistan, the growth rate of annual tourist visits, the cost of exported tourist services, the purpose of tourists' visits to our country, which region and which countries attract the most tourists. , were informed about the number of hotels served by them and their distribution by regions. The main directions of tourism in the country and their development were discussed.